Estratégias de extensão rural e uso de tecnologia agrícola entre pequenos produtores do Estado de Sergipe, no período de 1977 a 1979 - da Silva Motta, Joselito; M B Castro , Leda; Francis , David G; Muniz , José Norberto (Revista Ceres, 2025)
The main objectives of this study were to verify the relative increase in the use of agricultural technology by small farmers assisted by the Rural Extension Service in areas of the State of Sergipe, during the period 1977 to 1979; to analyze the relationships between such increases and the strategies of Rural Extension as well as the consequences of the improved technology in terms of their gross income from agriculture.